If you give a pig a party - Numeroff, Laura Joffe; Bond, Felicia ([New York] : Laura Geringer Books, 2005)
One thing leads to another when you give a pig a party.
2.7
K-3
Keywords: Swine -- Juvenile fiction; Parties -- Juvenile fiction; Friendship -- Juvenile fiction; Pigs -- Fiction; Parties -- Fiction; Friendship -- Fiction; Pigs -- Fiction; Parties -- Fiction; Friendship -- Fiction